Recognition and duration of illness in adolescent eating disorders: Parental perceptions of symptom onset. Issue 8 (26th August 2021) - Rosello, Rocio; Gledhill, Julia; Yi, Irene; Watkins, Beth; Harvey, Lucy; Hosking, Alexandra; Nicholls, Dasha
Abstract: Aim: To understand the earliest parent reported signs suggesting their child may have an eating disorder (ED), and to quantify time from symptom onset to specialist assessment. Methods: This is a secondary analysis of data derived from parents of 78 young people presenting to a British community ED service who completed a questionnaire asking when they first noticed their child displaying (a) a change in eating pattern, (b) weight concerns, (c) shape concerns. Parents were also asked to describe the first thing they noticed in terms of possible ED symptoms. Results: Mean age was 14.9 (SD: 1.58), 94% were female with diagnoses of anorexia nervosa ( n  = 50), bulimia nervosa ( n  = 10) and atypical anorexia nervosa ( n  = 18). Weight and shape concerns were most often noticed over a year prior to assessment (mean 12.7 months [SD: 12.8] and 13.3 months [SD: 13.2], respectively), with eating pattern change observed a mean of 9.7 months (SD: 7.6) before referral to specialist care. Seven main themes were developed from parents' descriptions of their child's symptoms: (1) eating pattern change, (2) shape concern, (3) weight concern, (4) observed weight loss, (5) binge eating/compensatory behaviours, (6) other mental health concerns and (7) physical symptoms. Conclusions: The most common parental concerns were eating pattern change, specifically their child becoming more rigid/rule‐bound with regard to eating and dietary restraint. Such external changes are likely observed before physical changes such as weight loss, offering potential for early identification by parents, primary care and other professionals, with implications for improved prognosis.